Chile - Financial Sector Assessment Program, October 2021 : Technical Note - Competition in the Financial Sector - Cohen, Charles; Dijkman, Miquel (World Bank, Washington, DC, 2022)
This note assesses competitive dynamics and potential impediments in Chile’s financial sector in order to provide actionable policy recommendations. This note contains both a quantitative as well as qualitative assessment of competition. The quantitative assessment explores market characteristics and dynamics, including market structure and concentration, cross-ownership and vertical integration, and customer conditions/consumer power. The quantitative assessment is complemented by a qualitative analysis of the regulatory and institutional framework to understand how private and public interventions shape market dynamics and result in specific market outcomes, including efficiency, degree of market power and consumer mobility (Figure 1). The note will focus primarily on the retail banking sector as well as payment systems and discuss competitive dynamics in other parts of the financial sector only to the extent that they affect these two areas, for example in the context of financial conglomerates.